Studi Strategi Pemasaran Selama Masa Pandemi Covid 19 Pada UMKM Olahan Tempe Semarang - Syamsul Hadi; Yuniarto Rahmad Satato; Mochamad Ainan (LPPM Universitas Sains dan Teknologi Komputer, 2022)
This research is a type of field research, where the author goes directly to the field in processed tempeh SMEs in Tempe Processed Village, Sampangan Village, Gajah Mungkur District, Semarang City. The study used data analysis techniques, namely qualitative methods with a descriptive approach. In analyzing the data, the researcher conducted observations, interviews, and documentation to obtain the required data. The results showed that to survive the COVID-19 pandemic, the efforts made were marketing through social media, promotion through social media and maintaining the quality of products and services from Tempe Processed SMEs.